Myostatin: genetic variants, therapy and gene doping - André Katayama Yamada; Rozangela Verlengia; Carlos Roberto Bueno Junior (Brazilian Journal of Pharmaceutical Sciences, 2012)
Since its discovery, myostatin (MSTN) has been at the forefront of muscle therapy research because intrinsic mutations or inhibition of this protein, by either pharmacological or genetic means, result in muscle hypertrophy and hyperplasia. In addition to muscle growth, MSTN inhibition potentially disturbs connective tissue, leads to strength modulation, facilitates myoblast transplantation, promotes tissue regeneration, induces adipose tissue thermogenesis and increases muscle oxidative phenotype. It is also known that current advances in gene therapy have an impact on sports because of the illicit use of such methods. However, the adverse effects of these methods, their impact on athletic performance in humans and the means of detecting gene doping are as yet unknown. The aim of the present review is to discuss biosynthesis, genetic variants, pharmacological/genetic manipulation, doping and athletic performance in relation to the MSTN pathway. As will be concluded from the manuscript, MSTN emerges as a promising molecule for combating muscle wasting diseases and for triggering wide-ranging discussion in view of its possible use in gene doping. Desde sua descoberta, a miostatina (MSTN) entrou na linha de frente em pesquisas relacionadas às terapias musculares porque mutações intrínsecas ou inibição desta proteína tanto por abordagens farmacológicas como genéticas resultam em hipertrofia muscular e hiperplasia. Além do aumento da massa muscular, a inibição de MSTN potencialmente prejudica o tecido conectivo, modula a força muscular, facilita o transplante de mioblastos, promove regeneração tecidual, induz termogênese no tecido adiposo e aumenta a oxidação na musculatura esquelética. É também sabido que os atuais avanços em terapia gênica têm uma relação com o esporte devido ao uso ilícito de tal método. Os efeitos adversos de tal abordagem, seus efeitos no desempenho de atletas e métodos para detectar doping genético são, contudo, desconhecidos. O objetivo da presente revisão de literatura foi discutir biossíntese, variantes genéticas, manipulação genética e farmacológica, e doping relacionado à via da MSTN. Como será concluído do manuscrito, a MSTN emerge como uma molécula promissora para combater doenças atróficas musculares e para gerar muitas discussões devido à sua possível utilização em doping genético.